La necesidad de reformar la Ley Orgánica De Transporte Terrestre, Transito, Y Seguridad Vial, en la relación a la sanción que suspende por 60 días a las operadoras de transporte a las cuales pertenecen las unidades siniestradas - Barreno Guijarro, Héctor Ricardo (2016)
The Organic Law of Land Transport, Traffic and Road Safety, determines if a driver, or a unit of an operator or cooperative transport is involved in the commission of an offense or a traffic accident, is punishable the operator with the suspension of the operating permit for a fixed period or even permanently. The suspension of the operating permit carriers to transport, involves the application of a sanction that seriously injures the rights of other members of the cooperative who are disabled during the time of suspension or final form of labor in the provision of public transport, which causes the violation of the right to work recognized in the Constitution of the Republic of Ecuador and even in international legal instruments. Similarly to suspend the operating license and impeding the exercise of the right to work is in contravention of a constitutional principle for the exercise of the rights of individuals, as is that no legal rule may restrict the rights and guarantees recognized in the Constitution of the Republic of Ecuador. The violation of the right to work and the contradiction of momentous constitutional principles by the effect of the suspension of the operating permit to transport operators, creates legal and social issues, which is studied in this paper which is entitled: "THE NEED FOR REFORMING THE ORGANIC LAW OF LAND TRANSPORT, TRANSIT AND ROAD SAFETY IN RELATION TO SANCTION THAT SUSPENDED FOR 60 DAYS TO TRANSPORT OPERATORS TO WHICH BELONG TO UNITS stricken" The investigation conforms in all its parts with the rules laid down in the Regulations of Academic Board of the National University of Loja, and concludes with some proposals for reform of the Organic Law of Land Transport, which is aimed at suppressing the possibility of apply the suspension of the operating permit to transport operators, in order to guarantee the right to work of those involved in the delivery of public service, as members of these cooperatives